2019
DOI: 10.3892/etm.2019.8247
|View full text |Cite
|
Sign up to set email alerts
|

Expression and correlation of Chemerin and FABP4 in peripheral blood of gestational diabetes mellitus patients

Abstract: Expression and correlation of Chemerin and fatty acid-binding protein 4 (FABP4) in peripheral blood of gestational diabetes mellitus (GDM) patients were investigated. Sixty patients with GDM from March 2018 to March 2019 in the People's Hospital of Zhangqiu Area were selected as the study group (SG) and another 50 healthy pregnant women corresponding to their age and pregnancy were selected as the control group (CG). Enzyme linked immunosorbent assay (ELISA) was used to detect the expression of Chemerin and FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…This link between GDM and two members of the sFRP protein family implicates a role of the Wnt signaling pathway in impaired glucose tolerance. Furthermore, our results are in concordance with previous studies that showed decreased Adiponectin concentrations [37,38,61] and increased Chemerin and Leptin concentrations [32,36,41,62] in the first trimester of pregnancy in women who later developed GDM. In contrast to T2DM, it is proposed that GDM has a hormonal and autoimmunological background as underlying pathological mechanism [6][7][8][9][10][11][12].…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…This link between GDM and two members of the sFRP protein family implicates a role of the Wnt signaling pathway in impaired glucose tolerance. Furthermore, our results are in concordance with previous studies that showed decreased Adiponectin concentrations [37,38,61] and increased Chemerin and Leptin concentrations [32,36,41,62] in the first trimester of pregnancy in women who later developed GDM. In contrast to T2DM, it is proposed that GDM has a hormonal and autoimmunological background as underlying pathological mechanism [6][7][8][9][10][11][12].…”
Section: Plos Onesupporting
confidence: 93%
“…Adiponectin is an adipocytokine abundantly present in the circulation and involved in regulating glucose concentrations as well as fatty acid breakdown [39,40]. Moreover, higher Chemerin and Leptin concentrations during early pregnancy have also been shown to be associated with the development of GDM suggesting that these two adipocytokines can also be used as predictive biomarkers of GDM [32,41]. Chemerin modulates adipogenesis and immune system functions by binding to its own receptor [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some authors did not observe any significant correlations between those parameters [ 177 ], the others found that chemerin values were positively markedly correlated with HOMA-IR or insulin levels [ 172 , 179 , 180 , 181 ]. Chemerin values were also found to be positively correlated with fatty acid-binding protein 4, interleukin-6, and tumor necrosis factor-α [ 182 ].…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
“…To analyze its utility in the prediction of GDM, it is crucial to evaluate its blood concentrations in patients with GDM and healthy individuals. Some authors found that chemerin concentrations in peripheral blood are significantly increased throughout the pregnancy in patients with GDM [ 172 , 177 , 179 , 182 , 183 , 184 , 185 ]. Whereas some studies reported that chemerin levels are also significantly elevated in the cord blood samples [ 172 , 186 ], the others did not find any differences [ 187 ].…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
See 1 more Smart Citation